2002
DOI: 10.2355/isijinternational.42.1477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Alloying on the Pitting of Type 310 Stainless Steel.

Abstract: The effect of nitrogen alloying on the pitting behavior of type 310 stainless steel has been investigated through measurements of pitting potential (E ' pit ) as a function of temperature and concentration of NaCl (C NaCl ). Nitrogen was effective to shift E ' pit to nobler direction especially at temperatures below critical one. The critical pitting temperature was defined as the temperature below which the usual linear relationship between E ' pit and logarithm of C NaCl did not stand. Alloying the stainless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…It has been also proposed that NH 4 + may react with free chlorine in chlorinated water, forming less oxidising species (Ives, Lu, & Luo, 1991). Moreover, it has been suggested that NH 4 + could form corrosion inhibiting nitrates (Baba & Katada, 2006;Yashiro, Hirayasu, & Kumagai, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It has been also proposed that NH 4 + may react with free chlorine in chlorinated water, forming less oxidising species (Ives, Lu, & Luo, 1991). Moreover, it has been suggested that NH 4 + could form corrosion inhibiting nitrates (Baba & Katada, 2006;Yashiro, Hirayasu, & Kumagai, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The dissolution gives rise to the formation of NO 3 − at noble potential [14,[25][26][27][28]. Yashiro et al [28] clarified that the amount of NO 3 − increased after the polarization at elevated potential as high as 0.55 V (SCE). From the point of view, it is possible to think the following reaction on the cathode side, where the polarization tests were done at 600 mV (SCE)…”
Section: Thementioning
confidence: 99%
“…inhibition is the existence of a high passivation potential [8,[26][27][28]. It has also been suggested that there is a system dependent critical passivation potential below which inhibition of localized corrosion by NO 3 will not take place [26].…”
Section: An Interesting Observation Made By Numerous Authors About Nomentioning
confidence: 99%
“…Another suggested mechanism involves the reduction of NO 3 to atomic nitrogen [23,28,34,35]. The N that is formed may then proceeds to adsorb to a de-passivated metal surface (or to weak points on the oxide film) to promote oxide film formation [35].…”
Section: -mentioning
confidence: 99%